Composition, insecticidal activity and other biological activities of Tanacetum abrotanifolium Druce. essential oil - Polatoglu, Kaan; Karakoc, Omer Cem; Yucel, Yasemin Yucel; Demirci, Betul; Goren, Nezhun; Baser, Kemal Husnu Can (ELSEVIER, 2015)
Essential oils from flower and stem of Tanacetum abrotanifolium Druce. (Asteraceae), from Turkey were investigated for their insecticidal and biological activity. Oils produced considerable activities in insecticidal activity and AChE inhibition assays. Highest contact toxicity against Sitophilus granarius was observed in flower oil (8130%). The stem oil also produced considerable contact toxicity against S. granarius (47.77%). AChE enzyme inhibition of the flower oil (20 mu L) T. abrotanifolium is found to be 85.3% which is not greater than the inhibition observed for galanthamine at 8.3 mu M concentration (86.0%). The oils also produced low phytotoxic activity against Lemna minor and in DPPH (2,2-diphenyl-1-picrylhydrazyl) scavenging and PRAP (phosphomolybdenum reducing antioxidant power) assays. The highest growth inhibition against L. minor was observed for flower oil at 10 mg/mL oil/petri dish (38.14%). The highest DPPH scavenging activity (42.30%) and phosphomolybdenum reducing activity (234.70 AU - TLC densitometry) was observed also for the stem oil at 10 mg/mL concentration. Both DPPH scavenging and PRAP activities were very low for this oil when compared with positive controls at the same concentration. Flower and stem oils were analyzed by gas chromatography (GC) and gas chromatography/mass spectrometry (GC/MS). The flower and stem oils of T. abrotanifolium were characterized with camphor 35.2%, (E)-sesquilavandulol 19.0%, 1,8-cineole 13.5% and hexadecanoic acid 41,8%, (E)-sesquilavandulol 16.2%, tetradecanoic acid 6.6%, respectively. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Tanacetum abrotanifolium; Essential oil composition; Sitophilus granarius toxicity; Lemna minor fumigant toxicity; AChE enzyme inhibition; HPTLC-PRAP activity; SITOPHILUS-GRANARIUS; ENANTIOMERIC DISTRIBUTION; BOTANICAL INSECTICIDES; MAJOR COMPONENT; SCHULTZ BIP.; IN-VITRO; L.; COLEOPTERA; VULGARE; ACETYLCHOLINESTERASE; Agriculture